Accurate and Simplified Dielectric Modeling Based on Depolarization Current Analysis - Peerawut Yutthagowith; Phetai Nimsanong; Yoshihiro Baba (IEEE Transactions on Industry Applications, 2026)
This paper improves a previously developed approach for accurately modeling the dielectric equivalent circuit of high-voltage equipment. While preserving its simplicity, the enhanced method improves precision, enabling the accurate fitting of depolarization current, which is then used to determine the dielectric loss factor with higher accuracy. To assess its effectiveness, extensive test cases were conducted, and the results were systematically compared with those obtained using both the previously proposed approach and commercial software solutions. The comparative analysis confirms that the enhanced method delivers high accuracy, achieving a similar relative root mean square error while yielding a lower root mean square relative error for the depolarization current. These results emphasize the effectiveness and practicality of the proposed technique in modeling the equivalent circuit for dielectric analysis. By offering a reliable and robust approach, this method enhances the evaluation of insulation performance in high-voltage applications.
Keywords: Power Transformer Diagnostics and Insulation; High voltage insulation and dielectric phenomena; Lightning and Electromagnetic Phenomena